2008
DOI: 10.1128/ec.00434-07
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interactions between the Paf1 Complex and a Cleavage and Polyadenylation Factor Are Revealed by Dissociation of Paf1 from RNA Polymerase II

Abstract: The Paf1 complex (Paf1, Ctr9, Cdc73, Rtf1, and Leo1) is normally associated with RNA polymerase II (Pol II) throughout the transcription cycle. However, the loss of either Rtf1 or Cdc73 results in the detachment of the Paf1 complex from Pol II and the chromatin form of actively transcribed genes. Using functionally tagged forms of the Paf1 complex factors, we have determined that, except for the more loosely associated Rtf1, the remaining components stay stably associated with one another in an RNase-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(136 citation statements)
references
References 60 publications
5
128
1
2
Order By: Relevance
“…Prelich and co-workers demonstrated several years ago that deletion of several PAF complex members, cdc73⌬, ctr9⌬, or paf1⌬, resulted in a decrease in H3K36me3 (49). Similarly, Jaehning and co-workers showed that CTD Ser 2 phosphorylation is reduced in these same three PAF mutants (44). Our data show that Set2 protein levels are also decreased in cdc73⌬, ctr9⌬, and paf1⌬ strains (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Prelich and co-workers demonstrated several years ago that deletion of several PAF complex members, cdc73⌬, ctr9⌬, or paf1⌬, resulted in a decrease in H3K36me3 (49). Similarly, Jaehning and co-workers showed that CTD Ser 2 phosphorylation is reduced in these same three PAF mutants (44). Our data show that Set2 protein levels are also decreased in cdc73⌬, ctr9⌬, and paf1⌬ strains (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Set2 protein levels were noticeably decreased in mutants of the PAF complex, which is known to play an important role in transcription elongation and affect CTD Ser 2 phosphorylation (Fig. 3B) (44). Significantly, Set2 protein levels were only decreased in PAF mutants that also exhibited changes in CTD Ser 2 phosphorylation, cdc73⌬, paf1⌬, and ctr9⌬.…”
Section: Set2mentioning
confidence: 81%
“…Previous studies showed that Paf1 and Ctr9 are important for Paf1C stability and integrity (26,28). To eliminate the residual Paf1C that forms in the absence of Rtf1 (29) and test the effect on HMD activity, we transformed the NLS-Myc-HMD expression plasmid into rtf1Δ paf1Δ and rtf1Δ ctr9Δ double mutants. Remarkably, even in the absence of Paf1 or Ctr9, the HMD behaved similarly to fulllength Rtf1 and was sufficient to direct H2B K123 ubiquitylation, H3 K79 dimethylation/trimethylation, and H3 K4 dimethylation, although at a reduced level compared with strains containing both Paf1 and Ctr9 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Paf1C-which in budding yeast consists of the subunits Paf1, Ctr9, Cdc73, Rtf1, and Leo1-impacts RNA synthesis at multiple stages (21). Paf1C associates with RNA pol II from the 5′ end of a gene to the poly(A) site (22,23); interacts functionally and physically with the transcription elongation factors Spt4-Spt5/DSIF, Spt16-Pob3/FACT, and TFIIS (8,(24)(25)(26)(27); regulates the phosphorylation state of RNA pol II (28,29); and is required for proper 3′ end formation of certain transcripts (30)(31)(32). Important to this study, deletion of RTF1 from yeast cells causes dramatic reductions in H2B K123 ubiquitylation and H3 K4 and K79 methylation (33)(34)(35)(36), and this role in histone modification, like other Paf1C functions, is conserved in higher eukaryotes (37)(38)(39)(40).…”
mentioning
confidence: 99%
“…For example, the C-terminal domain (CTD) of the RNAPII largest subunit also plays an important role in 39-end processing, likely by mediating interactions with 39-end processing factors (McCracken et al 1997;Hirose and Manley 1998;Barilla et al 2001;Fong and Bentley 2001). The Paf1 complex (Paf1C), which was first identified in yeast as an elongation factor and plays a role in transcription-associated chromatin modification (Krogan et al 2002;Squazzo et al 2002;Simic et al 2003;Mueller et al 2004;Rozenblatt-Rosen et al 2005), has been shown to be involved in mRNA 39-end formation (Penheiter et al 2005;Rosonina and Manley 2005) by interacting with CPSF, CstF, and symplekin (Nordick et al 2008;Rozenblatt-Rosen et al 2009). It is notable that one Paf1C subunit, Cdc73 or parafibromin, has been identified as a tumor suppressor protein, and the Paf1 protein is overexpressed in many cancers (Chaudhary et al 2007).…”
Section: -End Processing Machinerymentioning
confidence: 99%